2005
DOI: 10.1159/000084067
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Cardiac Troponin T and Echocardiography in the Diagnosis of Hypoxic Myocardial Injury of Full-Term Neonates

Abstract: Background: Perinatal asphyxia constitutes a significant problem influencing neonatal mortality and morbidity. Objectives: The aim of the present work was to provide evidence of the usefulness of cardiac troponin T (cTnT) and echocardiographic investigations in the diagnosis of heart damage in full-term infants after intrauterine hypoxia. Material and Methods: The subjects were 39 asphyxiated and 44 term infants without fetal anoxia. Quantitative determinations of cTnT were performed between 12 and 24 h of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
1
36
0
2
Order By: Relevance
“…Neonates who suffer respiratory distress demonstrate elevation of cTnT. Recently, it has been shown that a cTnT value of 1 0.1 g/l (ng/ml) was a reliable marker of myocardial injury demonstrated by tricuspid insuffi ciency by two-dimensional Doppler and color Doppler imaging in asphyxiated neonates [16] .…”
Section: Cardiac Troponin Measurements In Neonatesmentioning
confidence: 99%
“…Neonates who suffer respiratory distress demonstrate elevation of cTnT. Recently, it has been shown that a cTnT value of 1 0.1 g/l (ng/ml) was a reliable marker of myocardial injury demonstrated by tricuspid insuffi ciency by two-dimensional Doppler and color Doppler imaging in asphyxiated neonates [16] .…”
Section: Cardiac Troponin Measurements In Neonatesmentioning
confidence: 99%
“…Wide consensus has been established on the clinical utility of troponins in adults with acute coronary syndrome [1,3,10,15] . Although cardiovascular compromise is common in term and preterm sick infants [3,[16][17][18][19] , troponins have not been used routinely in neonates.…”
mentioning
confidence: 99%
“…Although cardiovascular compromise is common in term and preterm sick infants [3,[16][17][18][19] , troponins have not been used routinely in neonates. Cardiac function has been demonstrated to be influenced by the severity of respiratory distress and its ventilatory management in this age group [1,20,21] .…”
mentioning
confidence: 99%
“…The authors of that study found cTnT to be the most useful tool for assessing myocardial injury. In their study, echocardiography appeared to be of less value, apart from its help in the frequent diagnosis of tricuspid insufficiency, reported earlier as being more common in newborns who had experienced asphyxia (46). However, Costa et al did report such a relationship between higher cTnT levels and echocardiographic signs of myocardial compromise in infants who had experienced asphyxia.…”
Section: Reviewmentioning
confidence: 80%